From optimal to stagnant growth: The role of institutions and culture - Panagiotis E. Petrakis; Dionysis G. Valsamis; Kyriaki I. Kafka (Journal of Innovation & Knowledge (JIK), 2017)
Optimal growth requires pro-growth institutions and culture. In an optimal growth pattern, institutions and culture facilitate entrepreneurship and innovation. In contrast, if the development and coevolution of institutions and culture are distorted, growth can become permanently stagnant, with a distorted creative destruction process causing weak entrepreneurship and innovation activity. Policymakers should therefore plan and implement pro-growth structural changes to institutions and culture that account for their coevolution process. Otherwise, imported growth (i.e., incoming capital flows or innovation) must be relied upon to form an exogenous pro-growth prototype that promotes growth, entrepreneurship, and innovation.
Keywords: D40; E02; E03; O00; O30; O43; Z10; 650; Institutions; Preferences; Culture; Optimal growth; Stagnant growth; Innovation